Calibrating Ukraine’s Growth Model: How Can Ukraine Emulate Poland’s Growth? - Kamyshnykova, Evelina (Comparative Economic Research. Central and Eastern Europe, 2024)
This study provides a comparative analysis of the economic growth paths of Ukraine and Poland from a growth‑model perspective and determines how to calibrate Ukraine’s growth model to converge with Poland’s booming economy. The methodology comprises an approach to operationalizing growth models for GDP growth decomposition into “import‑adjusted” demand components, drawing on national input‑output data from 2000 to 2019. I found that from 2000 to 2003, both European economies relied on a combination of exports and domestic consumption. Expanded trade integration and an FDI boost after Poland joined the EU in 2004 spurred the Polish growth model’s shift to a distinctively export‑led, FDI‑driven strategy with accelerated GDP growth rates. In Ukraine, in the wake of the great financial crisis, I identified a transition to a consumption‑led growth model that, along with a declining investment component of aggregate demand, led to fading growth rates. An analysis of sectoral contributions to GDP growth revealed that avoiding deindustrialization in Poland underpinned the country’s export‑led strategy, unlike Ukraine, which underwent a key sectoral shift from manufacturing to a commodities‑based orientation after 2008. Both these economies demonstrated a high level of integration into global value chains, focusing on labor‑intensive manufacturing and services, but Poland has outperformed Ukraine in terms of share of high value‑added exports, which increased after EU accession. Following the Polish pattern, I propose that Ukraine’s growth model should activate the FDI driver of economic growth, upgrading the export structure and moving up value chains to unlock the country’s growth opportunities. The study represents the first comparison of Ukraine’s and Poland’s economic growth paths that traces the changes in dominant final demand components and macro‑sectors in the two countries’ economic growth profiles. This paper contributes to the comparative political economy literature on the growth models of peripheral economies, providing insights that can inform policies for growth model transformation.